Maternal-perinatal characteristics and maternal behavior during labor in pregnant women with psychoprophylactic preparation - Idrugo-Castillo, Lesly Karolina (2023)
Objective: To identify the perinatal maternal characteristics and the behavior during labor of Peruvian pregnant women with the preparation in the obstetric psychoprophylaxis, 2018. Material and method: Observational, descriptive cross-sectional study in the participation of 64 adults pregnant with psycho-prophylactic preparation (6 or more sessions of obstetric psychoprophylaxis) from a hospital in Lima, Peru. The behavior during labor, dimensioned by periods (dilation, expulsive and delivery), was evaluated using a validated checklist. The perinatal maternal characteristics were clinical history. The ethics committee of the institution approved it. Results: Among the main characteristics, 82.81% had the correct controls, 59.38% did not participate with a companion, and 95.31% did not present complications during the expulsive period. Predominantly, the Apgar at minute was 8 (51.56%) and 9 at 5 minutes (100%). 96.88% had skin contact with the neonate. The most repetitive behaviors were performed at the time of expulsion (95.31%) and delivery (93.75%), adequate personal care (92.19%) and vertical delivery (92.19%). The behavior was adequate in 54.69% during the period of dilatation, 64.06% in the period of expulsion and 71.88% in the period of delivery. Conclusions: The proportion of gestures with the appropriate behavior was based on each of the periods of labor.